ASSESSING THE INTERPRETATION OF THE ELEMENTS OF “DISPOSE” AND “CHILD” FOR PURPOSES OF ESTABLISHING THE OFFENCE OF CONCEALMENT OF BIRTH – S v Molefe 2012 (2) SACR 574 (GNP) - GP Stevens (Obiter, 2014)
“The woman went to Tembisa Hospital on Tuesday as she was bleeding … a nurse questioned her about whether she had an illegal abortion, but she claimed that she did not … police searched her house and found the foetus wrapped up in a jersey in the bath … the woman was arrested and detained in Tembisa cells”. The abovementioned passage sets the stage for the decision under discussion dealing with the crime of concealment of birth. The crime of concealment of birth was unknown in our common law but has, however, been an offence since 1845 when it was criminalized in terms of section 1 of Ordinance 10 of 1845. Currently the offence of concealment of births is regulated in terms of section 113 of the General Law Amendment Act 46 of 1935 which provides that “(1) Any person who, without a lawful burial order, disposes of the body of any newly born child with the intent to conceal the fact of its birth, whether the child died before, during or after birth, shall be guilty of an offence and liable on conviction to a fine or to imprisonment for a period not exceeding three years”. In order to incur criminal liability in terms of this offence, it is essential for the prosecution to prove all the elements of the offence which are that the accused had the intention to “dispose” of the dead body of the newly born “child” with the intention of concealing the fact of its birth. The problematic aspect in terms of the essential elements of the offence, relates to the fact that “dispose” and “body of a child”, are not defined in the Act. The case under discussion elucidates the meaning of these concepts and provides guidance as to the interpretation of these two elements.